Peran Status Zat Besi Dan Gizi Makro-Mikro Sebagai Determinan Risiko Infeksi Cacing Usus (STH) Pada Anak Di Daerah Endemis - Hidana, Rachma; Nababan, Diana Listy L.P.; Ridwan, Muhammad Rafif; Sidik, Ahmad Fajar; Pertiwi, Intan Putri; M, Nur Khalisha Yahya; Subkhi, M. Umar; Marcellino, Mario; Cesia, Maria Kasih; Naziihah, Naura Adhwa; Fajri, Andi Muhammad; Apsari, Shafira Nova (Barongko: Jurnal Ilmu Kesehatan, 2025)
Soil-Transmitted Helminths (STH) remain a significant public health problem in endemic areas, especially among children. STH infections contribute to decreased nutritional status, iron deficiency anemia, and growth and cognitive disorders. This literature review aims to analyze the relationship between iron status, macro- and micronutrient intake, and the risk of STH infection in children. Articles were searched through Google Scholar, PubMed, ScienceDirect, and Web of Science with inclusion criteria covering publications from 2015–2025, observational studies on children under 18 years old, and discussions on the link between nutritional status and STH. The results show that STH infections cause anemia through intestinal bleeding, malabsorption, and chronic inflammation that increases hepcidin levels. Deficiencies in protein, energy, iron, zinc, and vitamin A can weaken immunity and worsen the cycle of malnutrition. Relying solely on mass deworming programs is insufficient without improvements in sanitation, nutrition education, and supplementation of essential nutrients. It is expected that this review can serve as a basis for holistic intervention recommendations to reduce the prevalence of STH infections among children in endemic areas.